EXPLORING THE POLICY ISSUES IN MALAYSIA MY SECOND HOME PROGRAMME (MM2H): A POLICY ANALYSIS STUDY - Nurulhasanah Abdul Rahman, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Malaysia My Second Home Programme (MM2H) is not a new policy in the country. This programme has been implemented since 2002 and it is not a stranger to the foreign retirees and investors who chose Malaysia as their second home. Nevertheless, this programme attracted a spark of controversy due to its constant reviews that come with new requirements from time to time. As a result, the changes affected the potential applicants and the existing pass holders which hinder the programme’s achievement. With that, this study aims to explore the policy issues in the MM2H programme by coordinating suggestions from academicians and policy actors who are involved in the programme. By using a qualitative approach, three policy issues were found to influence the programme’s implementation success. Correspondingly, three recommendations are proposed related to the programme’s structure, the programme’s parent owner, and the empowerment of the MM2H Centre. Finally, this study offers a new dimension of policy studies by focusing on the progress of the MM2H programme which has not been evaluated since its establishment in 2002. Hence, this analysis is one of the pioneer studies that highlight the implementation of MM2H from the policy perspective.